The Clinical Usefulness of Nuclear Matrix Protein-22 in Patients with End-Stage Renal Disease and Microscopic Hematuria. (February 2013) - Trojan, Brandon; Tang, Andrew; Chandrapal, Jason; Filleur, Stephanie; Nelius, Thomas
<x xml:space="preserve">Abstract</x> Objectives: To evaluate the sensitivity, specificity, and false-positive rate of the nuclear matrix protein-22 (NMP22) test in patients with end-stage renal disease (ESRD) and microscopic hematuria in order to avoid unnecessary follow-up tests for patients with false-positive NMP22 test results. Patients and Methods: Patients with ESRD were screened for microscopic hematuria as part of the pre-transplant workup. Patients with documented microscopic hematuria underwent workup as recommended by the American Urological Association. Results: Between January 2006 and April 2012, 277 patients with ESRD were referred to the Department of Urology for pre-transplant evaluation. Fifty-seven (22.6%) patients were found to have microscopic hematuria and underwent further testing. Nineteen (33.3%) patients demonstrated a positive NMP22 test result and 38 (66.7%) had a negative NMP22 test result. The false-positive rate was 32.7%. The sensitivity and specificity of the NMP22 test in this patient population were 50% and 67%, respectively. The positive predictive value of the test was 52.6% and the negative predictive value 97.3%. Especially noteworthy, the two detected transitional cell cancers of the urinary bladder were both demonstrated during cystoscopy, independent of their NMP22 or urine cytology test result. Conclusions: Our study revealed a significantly increased NMP22 test false-positive rate, low sensitivity, and specificity in the setting of high prevalence of microscopic hematuria, proteinuria, and low glomerular filtration rate in patients with ESRD. Therefore, cystoscopy remains the gold standard for patients with ESRD and microscopic hematuria for pre-transplant evaluation.